2018
DOI: 10.1002/hpm.2517
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing inequality in financial protection situation in Iran after implementing the health reform plan: What does the evidence show based on national survey of households' budget?

Abstract: The headcount ratio of the exposure to catastrophic health expenditures in urban and rural households was 2.5% (2.43% - 2.64%) and 3.6% (3.48% - 3.76%), respectively. The difference in households' income levels was the main contributor in explaining the inequality in facing catastrophic health expenditures between poor and nonpoor households. [Correction added on 02 June 2018, after first online publication: The "Results" section of the Abstract of the published article has been correctly updated on this versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…Boing et al found that the poorest households and households headed by the leasteducated individuals significantly contribute to increasing social inequality [24]. Moradi et al showed that income is the most significant determinant of inequality in facing CHE [25]. Wang et al used a nationally representative dataset and found that household size, per capita income, family members above 65 years of age, and family members with two or more chronic diseases significantly increase CHE inequality [26].…”
Section: Introductionmentioning
confidence: 99%
“…Boing et al found that the poorest households and households headed by the leasteducated individuals significantly contribute to increasing social inequality [24]. Moradi et al showed that income is the most significant determinant of inequality in facing CHE [25]. Wang et al used a nationally representative dataset and found that household size, per capita income, family members above 65 years of age, and family members with two or more chronic diseases significantly increase CHE inequality [26].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of outpatient OOP, where Rad et al (2017) reported signi cant increase of OOP payments for outpatient care services increased after the HTP, which in uenced the total OOP (17). In addition, despite the increase in the share of health from GDP after the HTP in Iran, catastrophic and impoverishment expenditures have not decreased su ciently to achieve the goals of the HTP in term of the nancial risk protection (50).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis presents changes in the level and distribution of OOP payments and catastrophic health expenditure after the implementation of the HTP. Previous studies estimated the impact of HTP on OOP payments by using different methodologies and thresholds . The methodology used in the current study is described in the 2017 global monitoring report on progress towards UHC, which is more relevant to health reforms aimed at reaching universal health coverage.…”
Section: Discussionmentioning
confidence: 99%